ThinkingWisely, Acting Widely: Enhancing Critical Thinking Skills in Students - Baluashvili, Nino (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The paper aims to review existing research on critical thinking and develop targeted activities and exercises to enhance these skills in students. By synthesizing findings from multiple studies, the paper identifies common themes and effective practices in teaching critical thinking. Additionally, it explores the challenges and barriers faced by educators. Building upon this review, the paper proposes a set of practical activities and exercises specifically designed to enhance critical thinking abilities in students. These activities are crafted to be engaging and adaptable to different educational settings. The proposed exercises aim to stimulate analytical thinking, problem-solving, and reflective judgment among students. The paper concludes with practical recommendations for educators and educational institutions to implement these strategies, ultimately aiming to foster a generation of critical thinkers capable of navigating complex issues.